ANALISIS KESALAHAN SISWA KELAS IV DALAM MENYELESAIKAN SOAL MATEMATIKA BANGUN DATAR BERDASARKAN TIPE NOLTING SDN 125 PEKANBARU - Dia Junaidi, Rizki Ayu; Witri, Gustimal; Guslinda, Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the lack of understanding experienced by students when given a math problem during studying process and can be known by the errors they do. This error arises because the students face difficulties in solving mathematical problems, particularly those related to the perimeters and areas of geometry planes. By knowing the mistakes made by students, it is hoped that the teachers can pay attention to the stages or steps of completion in solving math problems in plane geometry. The teachers are also hoped to play an active role towards students as to provide understanding in mastering concepts/formulas related to plane geometry so that mistakes can be reduced and students' abilities increase as expected. The purpose of this research is to find out the errors that often occur in solving math problems in plane geometry according to the types of error by Nolting made by Grade IV students in SDN 125 Pekanbaru. This type of research is quantitative with descriptive methods. The sample in this study consists of 44 students. Data collecting in this research was carried out through tests and interviews. The research instrument was in the form of a plane geometry test sheet. The research data were analyzed descriptively. After research conducting and data analysis, it can be concluded that errors often made by students are concept errors by 23%, application errors by 16%, careless errors by 9%, test procedure errors by 9%, and errors in misinterpreting instructions misread direction errors by 7%.Key Words: Student Error, Plane Geometry, Error Types by Nolting